THE USE OF FLASHCARD MEDIA TO IMPROVE ENGLISH VOCABULARY IN CLASS VII A STUDENTS OF MTsN 2 MALANG - Novitasari, Elma Diana; Ahmadi, Ahmadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to apply flashcard learning media in an effort to increase English vocabulary in class VII A MTsn 2 Malang. The method that the author uses is classroom action research, by observing the use of media in the classroom. The results of the study, flashcard learning media are cards with interesting words or pictures that become a teacher's tool for children to play and learn, especially in improving vocabulary understanding. The results of the schools taught by the researchers were very good, and there was an increase from the first cycle to the second cycle. The average value in the first cycle was 82, with learning completeness about 76% while in the second cycle it increased with an average value of 86 , with learning completeness around 86%, the results of the study show that the implementation of learning using flashcard media can improve student learning outcomes in English subjects in class VII MTsN 2 Malang